The Effect of Price, BPOM, and Halal Labels on College Students’ Skincare Purchase Decisions - Fathin Fadhillah; Nurjannah Nurjannah; Tajul ‘Ula; Mastura Mastura (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2025)
This study aims to determine the effect of price, BPOM labeling, and halal labeling on purchasing decisions for skincare products among female students of the Faculty of Islamic Economics and Business, IAIN Langsa. The method used is a quantitative approach. This study uses a total sampling technique with the sample used being female students at the Faculty of Islamic Economics and Business, IAIN Langsa, Class of 2021, totaling 135 respondents. The data collection technique used a questionnaire. The data analysis method used multiple linear regression, classical assumption test, and hypothesis test (t-test, F-test, and R2). The results of the study showed that partially the variables price, BPOM labeling, and halal labeling had a significant positive effect on purchasing decisions for skincare products among female students of the Faculty of Islamic Economics and Business, IAIN Langsa. Price, BPOM labeling, and halal labeling are used simultaneously in purchasing decisions for skincare products among female students of the Faculty of Islamic Economics and Business, IAIN Langsa.